The immunological role of mesenchymal stromal cells in patients with myelodysplastic syndrome - Zheng, Likun; Zhang, Lei; Guo, Yixuan; Xu, Xintong; Liu, Zhaoyun; Yan, Zhenyu; Fu, Rong (Frontiers in Immunology, 2022)
Myelodysplastic syndrome (MDS) is a common hematological malignant disease, characterized by malignant hematopoietic stem cell proliferation in the bone marrow (BM); it manifests clinically mainly by pathological hematopoiesis, hemocytopenia, and high-risk transformation to acute leukemia. Several studies have shown that the BM microenvironment plays a critical role in the progression of MDS. In this study, we specifically evaluated mesenchymal stem cells (MSCs) that exert immunomodulatory effects in the BM microenvironment. This immunomodulatory effect occurs through direct cell-cell contact and the secretion of soluble cytokines or micro vesicles. Several researchers have compared MSCs derived from healthy donors to low-risk MDS-associated bone mesenchymal stem cells (BMSCs) and have found no significant abnormalities in the MDS-MSC phenotype; however, these cells have been observed to exhibit altered function, including a decline in osteoblastic function. This altered function may promote MDS progression. In MDS patients, especially high-risk patients, MSCs in the BM microenvironment regulate the immune cell function, such as T cells, B cells, NK cells, Dendritic Celldendritic cells, neutrophils, myeloid-derived suppressor cells (MDSCs), macrophages, and Treg cells, thereby enabling MDS-associated malignant cells to evade immune cell surveillance. Alterations in MDS-MSC function include genomic instability, microRNA production, histone modification, DNA methylation, and abnormal signal transduction and cytokine secretion.